Risk Assessment of Factors Causing Production Delays in Precast Housing Panel Production - Saputra, Pungky Dharma; Mohammad Ichsan; Pambudi, Wisnu (Journal of Project Management Research, 2025)
Production delays are a common issue in the use of precast technology in construction. An evaluation of the completed production process indicates that delays occur at each stage of the precast housing panel production activities. The purpose of this research is to conduct a risk assessment of the factors causing production delays in precast housing panel production. The research object of this study is precast housing panels. This study is designed using a mixed-methods approach and will be conducted in two main phases: identifying risk factors causing production delays and assessing these risks. The risk identification process will involve experts providing expert judgment. Subsequently, a respondent survey will be conducted to assess the impact of each variable on production delays. Following the initial risk identification phase, the second phase involves a risk assessment analyzed using the Probability Impact Matrix (PIM). Ten risk variables have been identified as factors influencing production delays in precast housing panels. Among these, nine are categorized as high-risk variables, while one is classified as moderate risk. The identified risk variables include design, materials, equipment, human resources, management, finance, administration, weather, accidents, and force majeure, all of which impact production delays in precast housing panels. Based on the analysis using the Probability Impact Matrix (PIM), the high-risk variables, in descending order, are human resources, weather, force majeure, design, accidents, materials, equipment, finance, and administration. The moderate-risk variable, ranked last, is management.